أثر كفاءة وجودة الخدمات اللوجيستية على الصادرات في دول شمال إفريقيا خلال الفترة 2007-2019 - والي, طارق; طير, عبد الحق (جامعة الوادي - University of Eloued, 2023)
The study aims to measure the impact of the efficiency and quality of logistics services on exports in North African countries represented in Algeria, Tunisia, Morocco and Egypt, using (Panel Data Models) the period from 2007 to 2019, and by relying on the statistical program (Stata15). The results of the overall fixedeffects Panel model,showed an inverse relationship between the efficiency and quality of logistics services and exports in North African countries, while at the countries level the impact of the efficiency and quality of logistics services was positive on exports in Tunisia and Morocco, while the effect was negative in my countries Egypt and Algeria.
The Impact Of The Efficiency and Quality OfLogistics Services on Exportsin North African Countries 2007-2019
مقال
Keywords: مؤشر الأداء اللوجيستي ; كفاءة وجودة الخدمات اللوجيستية ; الصادرات ; نماذج بانل; logistic Performance Index, Efficiency and Quality of logistic Services, Exports, Panel Models